MicroRNAs 218a-5p, 219a-5p, and 221-3p regulate vestibular compensation - Mun Young Chang (Nature Portfolio, 2017)
Abstract Unilateral vestibular deafferentation (UVD) interrupts afferent signals from one side, resulting in an imbalance of the resting activity between bilateral vestibular nuclei. Vestibular compensation is the process of balancing the resting activity to reestablish homeostasis. Here, we investigated microRNAs (miRNAs) that regulate vestibular compensation using the Sprague–Dawley rat. After determining the progression of vestibular compensation following UVD, microarray analysis was performed and nine miRNAs were selected as candidates. Following validation by quantitative reverse transcription-PCR, three miRNAs remained. We assessed the effect of these miRNAs on vestibular compensation using miRNA oligomers. We compared the results of the rotarod test and 5-bromo-2′-deoxyuridine immunohistochemistry following UVD between the control group and the groups in which the candidate miRNA oligomers were administered. Administration of miR-218a-5p, 219a-5p, and 221-3p oligomers significantly affected vestibular compensation. Target pathway analysis of these miRNAs supported our results. Our findings suggest that the miRNAs 218a-5p, 219a-5p, and 221-3p regulate vestibular compensation.